Digital footprints as a factor in the security of personal data trafficking on the Internet - Bissaliyev, М.С.; Shakirov, К.Н. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2023)
The article discusses the main approaches to the use of knowledge about digital footprints on the Internet as a significant factor in ensuring the safe circulation of personal data in the cyber environment. The authors have made a review of the positions contained in the doctrine on this issue. The article contains definitions of digital traces, an algorithm for methods of encroaching on personal data using a global information network, and typical phases of such encroachment and the usual actions of the offender. For the first time in this field of knowledge, an integrated approach has been applied, combining both the achievements of the doctrine of information law and the forensic doctrine of traces. As a result, the authors have made proposals to adopt an international or regional (European) act providing standards for accessing special knowledge in case of detection of illegal access to personal data, including their “interception” as part of information exchange on the Internet.